The services of transport companies in international personal transportation on relation Czech Republic – Slovak republic. - Dacejová, Júlia; Zelený, Lubomír; Mervart, Michal, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
The master´s thesis deals with the international personal transportation on relation between Czech capital city, Prague and the biggest city of east Slovakia region, Košice. It aims mainly on services, which transport companies currently provide, and presents them according to their attractiveness from the customers´ point of view. The analysis of offered services enables us to describe quality of traveling between Prague and Košice. At the same time, it creates a picture about competition between operating companies on railways mainly. This paper focuses on railway transport but does not omit the bus transport neither. The end of the diploma thesis belongs to assessment of situation of current personal transportation and tries to forecast its future development.
Vedoucí práce: Lubomír Zelený
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses